PENGARUH KECERDASAN EMOSIONAL DAN KOMPETENSI TERHADAP KINERJA PEGAWAI DIMEDIASI ORGANIZATIONAL CITIZENSHIP BEHAVIOR PADA KANTOR PELAYANAN PAJAK PRATAMA SEMARANG TIMUR - Widayat, Hadi; Indarto, Indarto; Budiati, Yuli; Savitri, Fania Mutiara (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2023)
The Directorate General of Taxation is the agency responsible for managing state revenues through Service Offices in each region. Employees who work in the tax service office are required to perform well for the benefit of the institution. This study serves to analyze the relationship between emotional intelligence and competency on the performance of East Semarang Pratama Tax Service Office (KPP) employees with Organizational Citizenship Behavior as a mediating variable. This study used a quantitative method using a questionnaire to collect the data. The sample in this study is 108 obtained through the census method. The analysis used to process the data is regression analysis with SPSS 16. The results of this study indicate that emotional intelligence, competence and Organizational Citizenship Behavior affect employee performance. Emotional Intelligence and Competence also influence Organizational Citizenship Behavior. Furthermore, Organizational Citizenship Behavior is able to mediate the relationship between emotional intelligence and competency on employee performance.